Immature stages of two species of Evandromyia (Aldamyia) and the systematic importance of larval mouthparts within Psychodidae (Diptera, Phlebotominae, Psychodinae) - Pessoa, Felipe Arley Costa; Feitosa, Marlisson Augusto Costa; Castellón-Bermúdez, Eloy Guillermo; Ríos-Velásquez, Cláudia María; Ward, Richard Douglas (Zootaxa, 2008)
Phlebotomine sand flies (Diptera: Psychodidae) are vectors of Leishmania, Bartonella and several arboviruses. Sand fly taxonomy has been mainly based on adult morphological characters and few larval characters have been used. In this work the egg and all larval instars of Evandromyia carmelinoi (= Lutzomyia carmelinoi migonei group of authors) are described, as well as the fourth instar of E. lenti, two morphologically similar species. Scanning electron microscopy (SEM) and light microscopy were used to describe the species. The sand flies E. carmelinoi and E. lenti can be differentiated most readily by the antennae and the shoulder accessory b setae on the thoracic segments. Some information on the mouthpart morphology of Phlebotominae and Psychodinae that could be useful for future phylogenetic and systematic studies is also provided. Copyright © 2008 - Magnolia Press.
Keywords: Arbovirus; Bartonella; Diptera; Migonei Group; Phlebotominae; Psychodidae; Psychodinae